Urgensi Pendidikan Multikultural Di Indonesia Dalam Pendidikan Agama Islam - Novia Iffatul Izzah (Al Hikmah: Journal of Education, 2020)
Indonesia is a country that has ethnic diversity but has the same goal which is towards a just and prosperous society. That’s why, multicultural education development is important, an education process gives the same opportunity to all Indonesian without distinguishing the treatment because of the difference of ethnic, culture, and religion, that gives appreciation in diversity, and gives the same rights to a minority, in effort to strengthen unity, social identity, and national image in international. In this case, the school must design the learning process, prepare the curriculum, design evaluation, and prepare the teacher which has a perception and multicultural behavior and manner. So, becomes a part that gives a positive contribution to the students’ multicultural manner development.Indonesia merupakan sebuah Negara yang memiliki keragaman etnik tetapi memiliki tujuan yang sama, yakni menuju masyarakat adil makmur dan sejahera. Karena itu, menjadi penting pengembangan pendidikan multikultural, sebuah proses pendidikan yang memeberi peluang sama pada seluruh anak bangsa tanpa membedakan perlakuan karena perbedaan etnik, budaya, dan agama, yang memberikan penghargaan terhadap keragaman, dan yang memberikan hak-hak sam bagi etnik minoritas, dalam upaya memperkuat persatuan dan kesatuan, identitas sosial dan citra bangsa di mata dunia internasional. Dalam hal ini, sekolah harus mendesain proses pembelajaran, mempersiapkan kurikulum dan desain evaluasi, serta mempersiapkan guru yang meiliki persepsi, sikap dan perilaku multikultural, sehingga menjadi bagian yang memberikan konstribusi positif terhadap pembinaan sikap multikultural para siswanya.